2009
DOI: 10.1128/jvi.00318-09
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Replication Induces a DNA Damage Response Coordinated by DNA-Dependent Protein Kinase

Abstract: The parvovirus adeno-associated virus (AAV) contains a small single-stranded DNA genome with inverted terminal repeats that form hairpin structures. In order to propagate, AAV relies on the cellular replication machinery together with functions supplied by coinfecting helper viruses such as adenovirus (Ad). Here, we examined the host cell response to AAV replication in the context of Ad or Ad helper proteins. We show that AAV and Ad coinfection activates a DNA damage response (DDR) that is distinct from that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
140
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(149 citation statements)
references
References 91 publications
6
140
2
1
Order By: Relevance
“…S10). The pan-γH2AX staining has been reported to occur in human fibroblast cells subjected to Adeno-associated virus (58,60), Chlamydia (33), and UV and ionizing radiation (30,61,62). Recently, such nuclear-wide γH2AX has been shown to occur in highly DNAdamaged cells and is mediated by ATM kinase (30).…”
Section: Discussionmentioning
confidence: 99%
“…S10). The pan-γH2AX staining has been reported to occur in human fibroblast cells subjected to Adeno-associated virus (58,60), Chlamydia (33), and UV and ionizing radiation (30,61,62). Recently, such nuclear-wide γH2AX has been shown to occur in highly DNAdamaged cells and is mediated by ATM kinase (30).…”
Section: Discussionmentioning
confidence: 99%
“…ATR may be the principal kinase phosphorylating H2AX in these conditions, although ATM and DNA-PK also seem to be involved (Nichols et al, 2009). Pan-nuclear H2AX phosphorylation has also been observed in cells infected with the adeno-associated virus (AAV) (Collaco et al, 2009;Fragkos et al, 2008;Schwartz et al, 2009). The AAV genome, like that of Ad, consists of an ssDNA molecule with ITRs at both ends, resulting in the formation of double-hairpin structures (Brown, 2010).…”
Section: Ddr Induction By Dna Virusesmentioning
confidence: 90%
“…AAV replication in the presence of minimal Ad helper proteins induces a robust DDR-like response. This response is independent of the MRN complex and seems to be mediated principally by DNA-PKcs and, to a lesser extent, by ATM (Collaco et al, 2009;Schwartz et al, 2009). The response involves the accumulation of DNA-PK in compartments in which viral replication is occurring, and the pan-nuclear phosphorylation, not only of H2AX, but also of Smc1 and ATM (Schwartz et al, 2009).…”
Section: Ddr Induction By Dna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…The adenoviral components required in the lytic infection are E1a, E1b55k, E4orf6, DBP, and VAI. A series of adenovirus/AAV co-infection studies has provided significant insights into how DDR and DNA repair machinery play roles in AAV genome replication in the presence of adenovirus helper functions (Collaco et al, 2009;Schwartz et al, 2009). It has been shown that adenoviral E1b55k/E4orf6 degrades the MRN complex via the ubiquitin-proteasome pathway and E4orf3 mislocalizes the MRN complex to aggresome, abrogating the MRN function in triggering the ATM and ATR pathways (Figure 2a) (Collaco et al, 2009).…”
Section: Wtaav2 Genome Replication and Dna Repair Pathwaysmentioning
confidence: 99%